Ekplorasi dan Karakterisasi Biokimia Bakteri Resisten Timbal (Pb) dari Sungai Tallo Makassar - Fahruddin Fahruddin; Nur Haedar; Slamet Santosa; Sri Wahyuni (Fakultas Teknik, 2020)
Industrial progress and waste of urban domestic activities have an impact on the Pb heavy metal pollution on the environment, this will have an impact on human health. Pb metal can be overcome with biological methods by utilizing bacteria in reducing Pb metal. The study aimed to obtain the species of resistant bacterial isolates of Pb metal and determine its characteristics. Sediment and water samples were obtained from the Tallo River. Isolation and selection of Pb metal resistant bacteria were carried out on nutrient agar media is 10 ppm added of PbAgNO3, afterwards the colonies that grew and differed were characterized by morphological morphology and several biochemical tests. The characterization results obtained 8 isolates of Pb metal resistant bacteria consisted of 8 isolates from sediment samples and 3 isolates from water samples. The characteristics of each bacterial isolate on cell morphology are the same and biochemical tests show different results.